2002
DOI: 10.2307/1552465
|View full text |Cite
|
Sign up to set email alerts
|

Hydrology of Active Rock Glaciers: Examples from the Austrian Alps

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. INSTAAR, University of Colorado andThe Regents of the University of Colorado, a body corporate, contracting on behalf of the University of Colorado at Boulder for the benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
80
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(99 citation statements)
references
References 15 publications
17
80
0
2
Order By: Relevance
“…Slope angles in the initiation zones reach 27-41 (mean 32.6 ). Permafrost in the loose sediment of the eight catchments under investigation forms an impermeable layer which promotes drainage along preferential paths [Krainer and Mostler, 2002]. During rainstorms, water (and ice melt) is released to a torrent along the contact with the permafrost body.…”
Section: Study Regionmentioning
confidence: 99%
“…Slope angles in the initiation zones reach 27-41 (mean 32.6 ). Permafrost in the loose sediment of the eight catchments under investigation forms an impermeable layer which promotes drainage along preferential paths [Krainer and Mostler, 2002]. During rainstorms, water (and ice melt) is released to a torrent along the contact with the permafrost body.…”
Section: Study Regionmentioning
confidence: 99%
“…The insulating effects of the coarse debris cover of rock glaciers make them more resilient to climate warming compared to terrains overlain by more common fine-grained sediments and glaciers (Burger, Degenhardt, & Giardino, 1999;Harris & Pedersen, 1998;Scherler, Hauck, Hoelzle, & Salzmann, 2013). The discharge at the outlet of rock glaciers is typically characterized by low temperatures (e.g., <3°C) due to the low ground temperatures common to rock glaciers and the snowmelt-dominated hydrological regimes common in alpine areas where rock glaciers are present (e.g., Krainer & Mostler, 2002). Other coarse surficial deposits found in alpine areas, such as proglacial moraines and talus slopes, can have similarly low discharge temperatures (Clow et al, 2003;Millar, Westfall, & Delany, 2013;Roy & Hayashi, 2009;Roy, Zaitlin, Hayashi, & Watson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported the temperature of rock glacier outflows (Geiger, Daniels, Miller, & Nicholas, 2014;Krainer & Mostler, 2002;Millar et al, 2013;Williams, Knauf, Caine, Liu, & Verplanck, 2006;Winkler et al, 2016) but have not assessed these in the context of the catchment stream temperature. The overall purpose of this research is to evaluate the effects of rock glacier groundwater discharge on stream temperature and the associated implications for cold-water fish habitat.…”
Section: Introductionmentioning
confidence: 99%
“…While the hydrogeology of moraines, talus and hillslope aquifers has been the subject of intensive investigations (e.g., Clow et al 2003;Roy and Hayashi 2009;Muir et al 2011), knowledge about the hydraulic behavior and storage capacities of rock glaciers is sparse (Krainer and Mostler 2002;Krainer et al 2007;Millar et al 2013;Winkler et al 2016a). Nevertheless, rock glaciers are common landforms all around the globe in mountainous areas and at high latitudes-for instance, in the Austrian Alps, KellererPirklbauer et al (2012) and Krainer and Ribis (2012) have identified a total of 4,792 rock glaciers covering an area of about 286 km 2 .…”
Section: Introductionmentioning
confidence: 99%